ANALISIS DAN PENGUKURAN IT ALIGNMENT KASUS PADA PT. WILLIAM MAKMUR PERKASA - Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Entering the era of information and free trade, the company requires a certain superiority in the face of competition nationally and internationally. For every company that strives to provide the best service facilities for customers via the accuracy, precision and effectiveness information. These things must be supported by the development of information technology at the moment. Therefore, the information technology department to evaluate the results of implementing the system using a Maturity Model of COBIT (Control Objectives for Information and related Technology). Maturity Model is a way to measure how well the progress of the company's IT management processes. These measurements by using scales or limits (0 to 5) as a practical example in determining the levels of IT management capabilities at every level of ability. From the company level can be compared with the target company and references COBIT Maturity Model and reality on the ground.